TECHNOLOGIES OF PEDAGOGICAL INTERACTION: METHODS OF IMPLEMENTATION - Lovyanova, I.V. (Pedagogy of Higher and Secondary Education, 2008)
In article on base of the analysis of innovative processes, occurring in formation, is determined essence and place technology in hierarchies notion: paradigm, model, methods, technology. As one of the first step on way to new technology is considered realignment mechanism pedagogical interaction.